PROTOTYPE OF ARDUINO-BASED WATER LEVEL DETECTOR WITH ULTRASONIC SENSOR - Yanel, Karnova (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2023)
Most of the water can be found in the sea (salt water) and in the ice caps (at the poles and on the tops of mountains). Apart from that, water can also be found in clouds, rain, rivers, surface fresh water, lakes, water vapor, and sea ice. The water in these objects moves according to a water cycle, namely: through evaporation, rain, and the flow of water over the ground surface (runoff, including springs, rivers, estuaries) towards the sea. Floods are natural disaster events that occur when an excessive flow of water submerges land. Floods can occur within minutes or over a long period of time, and can last days, weeks, or longer. Floods are the most common and widespread of all weather-related natural disasters. The tool can function properly. The height can be set to be displayed with an LED light display. Can be applied to the floodgates to activate the motor driving the floodgates so that the water level through the floodgates can be adjusted in such a way.